Autonomic function and change in functional capacity in older adults: a longitudinal investigation - I-Chien Wu; Yung-Yi Lu; Wei-Ting Tseng; Pei-Fen Chen (Scientific Reports)
Abstract Functional capacity is an important objective health metric, and relies on the maintenance of physiological homeostasis. Autonomic nervous system is known to coordinates the maintenance of multi-organ homeostasis. The objective of this study was to examine the association of autonomic nervous system function with functional capacity in adults aged 55 years and older. A cohort of 542 adults (mean age of 70.1 years) received repeated measurements of heart rate variability, an autonomic nervous system function marker, and chair rise time, a functional capacity measure. Linear mixed models analysis showed that 1 SD lower powers in low-frequency range at baseline was associated with a 0.11 (95% CI 0.01–0.21) s/year faster increase in chair rise time during the follow-up, whereas 1 SD increase in powers in high-frequency range and 1 SD decrease in the ratio of powers in low-frequency range to powers in high-frequency range during the follow-up were associated with a 0.22 (95% CI 0.06–0.39) s and 0.17 (95% CI 0.01–0.33) s increase in chair rise time. In conclusion, autonomic nervous system function and its changes were longitudinally associated with changes in functional capacity in older adults.